Risk factors associated with the presentation of brucellosis in the spine - Pérez,Alberto Aceves (2015)
OBJECTIVE: The aim of this study is to describe the risk factors associated with the presentation of brucellosis on the spine, and determine the strength of association between these factors. METHODS: The medical records of patients with brucellosis on the spine were analyzed and a spreadsheet was created to compile the following data: age, sex, place of origin and residence, risk factors (exposure at work, consumption of unpasteurized products and comorbidities), clinical presentation (lumbar pain, anorexia, headache, myalgia, fatigue, paresthesia, dysesthesia, muscle weakness, weight loss, fever), affected spine level, presence of abscesses, disease duration (acute, subacute, chronic), laboratory studies (erythrocyte sedimentation rate, C-reactive protein, serology, blood culture, Rose Bengal test, histopathological reports), imaging studies (x-rays, MRI, bone gammagraphy), established treatment (medical and/or surgical), therapeutic failure and sequelae. RESULTS: A total of 17 patients, 10 women (58.8%) and seven men (41.2%), were reviewed from January 2007 to January 2011. The group had a mean age of 57.8 years with a standard deviation of +13.91 and age range between 16-74 years. CONCLUSIONS: There is no significant difference between the groups compared with respect to age and sex, however, improvement of the neurological deficit was observed in eight patients who underwent surgical procedure.